Adoption of planted forages by smallholder dairy farmers in coastal lowland Kenya - Mureithi, J.G.; Njunie, M.N.; Muinga, R.W.; Ali, R.; Thorpe, W.R.; Mwatate, C.D. (1998)
Smallholder dairy development in coastal lowland Kenya is mainly constrained by inadequate nutrition. Since the early 1960s, high quality forages have been introduced to improve feeding of dairy cattle in the region. A study was conducted to assess the contribution made by these forages to dairy cattle feeding and factors that influence their adoption. The study revealed that introduced forages contributed less than 40% and 25% of dairy cattle feeding during the rainy and dry seasons, respectively. Natural pasture grasses and broad-leaved weeds were the main feeds. However, farmers indicated that the natural forages were of poorer quality than the introduced ones. A major factor affecting adoption of the planted forages was the allocation of farm resources. Farmers gave preference to growing maize because it is the staple food crop in the region. Other factors farmers considered were: seasonal availability of natural forages; access to extension advice; availability of planting materials; profitability of farm enterprises; and availability and affordability of supplementary feeds.